Inovasi Perkelorat (Permen Kelor) Suplemen Gizi Tambahan Ramah Anak Di Desa Paddinging Kabupaten Takalar - Faradiba Faradiba; Rezki Amriati Syarif; Zainal Abidin; Rais Razak; Andi Amaliah Dahlia; Muzakkir Baits (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2026)
The stunting reduction program in Takalar Regency remains a priority for the government, including in Paddinging Village, which is a foster village of the Indonesian Muslim University. One solution to address stunting is to provide children with complete nutrition. Nutrient-rich Moringa leaves have been chosen to support dietary improvements. This community outreach aims to educate residents about stunting, how to prevent it, and the nutritional benefits of Moringa leaves. Women from the PKK in Paddinging Village received training on making Moringa jelly candies (Perkelorat) using nutrient-dense agar, rich in antioxidants and fiber, in forms and flavors appealing to children. They were also taught hygienic and attractive packaging methods. This program not only improves the PKK members’ knowledge and skills in producing and packaging Perkelorat, but it also offers them potential additional income. Results from this outreach and training showed highly satisfactory data, with 57.89% strongly agreeing that Perkelorat is an innovative product with a desirable chewy texture and sweetness, and expressed interest in continuing to consume and recommend it.